Relationship between Musculoskeletal Disorders and Level of Stress among Homemakers in Gujarat State: An Observational Study - Dhvani J. Teraiya; Krupa Tank (Indian Journal of Psychiatric Nursing)
Background: Women play a crucial role as family caregivers, engaging in HOUSEHOLD activities such as bending, kneeling, sitting, and repetitive hand motions. Musculoskeletal issues can arise from these various positions and movements, and these symptoms are linked to psychological and personal factors. The stress experienced may be an outcome of domestic responsibilities. Objective: The purpose of this study was to ascertain the association between stress levels and musculoskeletal disorders among Gujarati homemakers. Materials and Methods: After the ethical clearance, for data collection a designed Google Forms was spread across the Gujarat state through E-mail and social media platforms. Demographic details as well as both outcome measurement tools (Cornell musculoskeletal discomfort questionnaire and modified Perceived Stress Scale) were included in the shared Google Forms. Three hundred and thirty-two homemakers from Gujarat were selected as per the selection criteria. Results: The study findings revealed that musculoskeletal disorders were highly prevalent, affecting 87% of participants. Among these, the neck exhibited the highest prevalence at 39.65%, while the forearm had the lowest at 14.82%. Stress was also prevalent, with 49.65% experiencing moderate stress, 46.55% experiencing mild stress, and 3.79% experiencing high stress. A significant correlation was observed between musculoskeletal disorders and stress, with a correlation coefficient of 0.619 and a P-value of 0.00. Conclusion: The study concluded that the prevalence of musculoskeletal disorders was high with a moderate prevalence of stress. When musculoskeletal disorders correlate with stress, there was a positive relationship between musculoskeletal disorders and stress.